Bioethics institutionalisation in the Republics of Kosovo and Albania : legal, public-administrative, and social challenges - Haliti, Valdete (Array, 2021)
The paper tries to briefly present the thorny way of development of bioethics and bioethics institutionalisation in the two countries of South-East Europe – the Republics of Kosovo and Albania – with respect to legal, public-administrative, and societal parameters. Departing from a "European institutionalisation" primer, the article analyses the history and current situations in Kosovo and Albania, taking into account the most prominent individuals and ideas in the domain of bioethics institutionalisation. While Kosovo is missing the ratification of some basic documents (the Oviedo Declaration), Albania has a longer and richer experience in this field, but still lacks the diversity of approach so present and promising in the majority of European countries. Finally, recommendations for bioethical institutionalisation are provided, and the particular role of ethics in the development of public administration in the case of Kosovo is exposed in more detail.